Rationalizing energy level alignment by characterizing Lewis acid/base and ionic interactions at printable semiconductor/ionic liquid interfaces. Issue 1 (3rd December 2021) - Du Hill, Linze; De Keersmaecker, Michel; Colbert, Adam E.; Hill, Joshua W.; Placencia, Diogenes; Boercker, Janice E.; Armstrong, Neal R.; Ratcliff, Erin L.
Abstract : Chemical and ionic interactions between an ionic liquid and printable semiconductors are probed by photoelectron spectroscopy, with increasing reactivity associated with underlying defects from P3HT to NiO x to PbS/PbI x quantum dots to MAPbI3 . Abstract : Charge transfer and energy conversion processes at semiconductor/electrolyte interfaces are controlled by local electric field distributions, which can be especially challenging to measure. Herein we leverage the low vapor pressure and vacuum compatibility of ionic liquid electrolytes to undertake a layer-by-layer, ultra-high vacuum deposition of a prototypical ionic liquid EMIM + (1-ethyl-3-methylimidazolium) and TFSI − (bis(trifluoromethylsulfonyl)-imide) on the surfaces of different electronic materials. We consider a case-by-case study between a standard metal (Au) and four printed electronic materials, where interfaces are characterized by a combination of X-ray and ultraviolet photoemission spectroscopies (XPS/UPS). For template-stripped gold surfaces, we observe through XPS a preferential orientation of the TFSI anion at the gold surface, enabling large electric fields (∼10 8 eV m −1 ) within the first two monolayers detected by a large surface vacuum level shift (0.7 eV) in UPS. Conversely, we observe a much more random orientation on four printable semiconductor surfaces: methyl ammonium lead triiodide (MAPbI3 ), regioregular poly(3-hexylthiophene-2, 5-diyl (P3HT)), sol–gel nickel oxide (NiO x ), and PbI x -capped PbS quantum dots. For the semiconductors considered, the ionization energy (IE) of the ionic liquid at 3 ML coverage is highly substrate dependent, indicating that underlying chemical reactions are dominating interface level alignment (electronic equilibration) prior to reaching bulk electronic structure. This indicates there is no universal rule for energy level alignment, but that relative strengths of Lewis acid/base sites and ion-molecular interactions should be considered. Specifically, for P3HT, interactions are found to be relatively weak and occurring through the π-bonding structure in the thiophene ring. Alternatively, for NiO x, PbS/PbI x quantum dots, and MAPbI3, our XPS data suggest a combination of ionic bonding and Lewis acid/base reactions between the semiconductor and IL, with MAPbI3 being the most reactive surface. Collectively, our results point towards new directions in interface engineering, where strategically chosen ionic liquid-based anions and cations can be used to preferentially passivate and/or titrate surface defects of heterogeneous surfaces while simultaneously providing highly localized electric fields. These opportunities are expected to be translatable to opto-electronic and electrochemical devices, including energy conversion and storage and biosensing applications.